Application of osmoconvective dehydratation for the technological use of banana bark (Research, Society and Development, 2020)
The present study aims to perform osmoconvective dehydration of banana peels and to evaluate the influence of the variables (sucrose concentration and temperature) on the process. Fresh and dehydrated peels (optimized condition) were characterized according to the parameters: pH, total titratable acidity (ATT), total soluble solids (SST), SST/ATT ratio, water and total solids content, ashes, ascorbic acid, sugars. reducers, color (L*, a* and b*) and water activity (Aw). A 22 + 3 central point factorial design was performed to evaluate the effect of the input variables: sucrose concentration ranging from 40 to 60 °Brix and temperature from 40 to 60 °C on the response variables: water and mass loss, and solids gain in banana peels. The banana peels used in the experiments presented high water content and reasonable amounts of carbohydrates and ashes. The condition that presented the greatest reduction in water content and higher solids gains was using the temperature of 60 °C and 60 °Brix, being considered the optimized one. The osmoconvective dehydration process caused a greater incorporation of total soluble solids and higher percentages of total solids in the shells.